Time trends, associations and prevalence of blindness and vision loss due to glaucoma: an analysis of observational data from the Global Burden of Disease Study 2017. Issue 1 (6th January 2022) - Sun, Yi; Chen, Aiming; Zou, Minjie; Zhang, Yichi; Jin, Ling; Li, Yi; Zheng, Danying; Jin, Guangming; Congdon, Nathan
Abstract : Objective: To estimate global prevalence of blindness and vision loss caused by glaucoma, and to evaluate the impact of socioeconomic factors on it. Design: A population-based observational study. Setting: The prevalence of blindness and vision loss due to glaucoma were obtained from the Global Burden of Disease Study 2017 database. The Human Development Index (HDI), inequality-adjusted HDI and other socioeconomic data were acquired from international open databases. Main outcome measures: The prevalence of blindness and vision loss due to glaucoma by age, gender, subregion and Socio-Demographic Index (SDI) levels. Multiple linear regression analysis was performed to explore the associations between the prevalence and socioeconomic indicators. Results: The overall age-standardised prevalence of blindness and vision loss due to glaucoma worldwide was 81.5 per 100 000 in 1990 and 75.6 per 100 000 in 2017. In 2017, men had a higher age-standardised prevalence than women (6.07% vs 5.42%), and the worldwide prevalence increased with age, from 0.5 per 100 000 in the 45–49 year age group to 112.9 per 100 000 among those 70+. Eastern Mediterranean and African regions had the highest prevalence during the whole period, while the Americas region had the lowest prevalence. The prevalence was highest in low-SDI and low-income regions while lowest in high-SDI and high-income regions over the past 27 years. Multiple linear regression showed cataract surgery rate (β=−0.01, p=0.009), refractive error prevalence (β=−0.03, p=0.024) and expected years of schooling (β= -8.33, p=0.035) were associated with lower prevalence, while gross national income per capita (β=0.002, p<0.001) was associated with higher prevalence. Conclusions: Lower socioeconomic levels and worse access to eyecare services are associated with higher prevalence of glaucoma-related blindness and vision loss. These findings provide evidence for policy-makers that investments in these areas may reduce the burden of the leading cause of irreversible blindness.